Characterization of kidney damage using several renal biomarkers in dogs with naturally occurring heatstroke. Issue 2 (November 2015) - Segev, G.; Daminet, S.; Meyer, E.; De Loor, J.; Cohen, A.; Aroch, I.; Bruchim, Y.
Highlights: Based on renal biomarker analysis, acute kidney injury is invariably present in dogs with heatstroke. Kidney injury often goes unnoticed at presentation when using routine markers (e.g. serum creatinine). In dogs with heatstroke, both tubular and glomerular injuries were present. Abstract: Heatstroke is often associated with acute kidney injury (AKI). The objectives of this study were to characterize the kidney damage occurring in canine heatstroke using routine and novel biomarkers and to assess their diagnostic and prognostic performance. Thirty dogs with naturally occurring heatstroke were enrolled prospectively. Blood and urine specimens were collected at presentation, at 4 h post-presentation and every 12 h until discharge or death. The glomerular filtration rate (GFR) and electrolyte fractional excretion (FE) at 4 h post-presentation were also calculated, based on urinary clearances. AKI was further characterized by evaluating urine neutrophil gelatinase-associated lipocalin/creatinine ratio (UNGAL), urine retinol-binding protein/creatinine ratio (URBP), urine C-reactive protein/creatinine ratio (UCRP) and urine protein to creatinine ratio (UPC). These biomarkers were compared to those for 13 healthy dogs. Thirteen dogs (43%) died and 17 (57%) survived. Median serum creatinine concentration at presentation was 1.69 mg/dL (range, 0.5–4.7 mg/dL), while concurrent GFR was markedly decreased (median 0.60 mL/min/kg; range, 0.00–3.10 mL/min/kg). Median Na fractional excretion was 0.08 (range, 0.01–0.41) and was an accurate predictor of AKI (area under curve 0.89; 95% confidence intervals 0.76–1.00). Median UPC at presentation was 4.8 (range, 0.4–46.0). Median UCRP, URBP and UNGAL were increased in all dogs with heatstroke, and were mean 232, 133, and 1213-fold higher than healthy control dogs, respectively. In conclusion, although AKI occurs invariably in dogs with heatstroke, it is often subclinical at presentation. Damage occurs in both the renal tubules and the glomeruli. Novel kidney function tests for the characterization of renal injury and its severity are superior to conventional markers and could be used to facilitate early diagnosis of AKI.